Sosialisasi dan Motivasi Pentingnya Menabung Kepada Anak-anak Sejak Usia Dini untuk Bekal Masa Depan - Suci Rosmadewi; Endang Isnaini; Anis Fadhilah Pramono; Salman Nasution (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
KKN Mandiri is a real work lecture activity carried out by students individually. It aims to increase awareness and understanding of early childhood children about the importance of saving as a provision for the future. The activity was carried out in two schools, namely Nur Ilmi Kindergarten, Jaranguda Village and Muhammadiyah 01 Medan Mandala Islamic Senior High School. Through socialization and motivation to save, it is hoped that children can develop a habit of living frugally and being responsible in managing money from an early age. The methods used in this activity include lectures, discussions, questions and answers, and making creative piggy banks from recycled materials. This activity is designed to provide an understanding that is easily accepted by children with a fun and interactive approach. The results of this community service activity show an increase in students' understanding of the benefits of saving. Students become more enthusiastic in setting aside their pocket money to save, both in piggy banks and in the bank. Through making creative piggy banks, students gain direct experience in the practice of saving and feel motivated to continue this habit at home. In addition, the involvement of parents and teachers also strengthens the positive impact of the program, where they are expected to continue to support children in saving. The conclusion of this activity is that the socialization of saving in early childhood has a positive impact in raising awareness of the importance of saving. The creative approach taken has proven effective in motivating students to start saving. This program is expected to be a foundation for children in forming good financial habits in the future. Continuous support from schools and families will greatly assist in maintaining the sustainability of saving habits in children.